2009
DOI: 10.1186/1743-422x-6-46
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and geographical differences in HLA associations with the outcome of hepatitis C virus infection

Abstract: The associations of HLA-A*02 and HLA-DRB1*12 with HCV infection are opposite with different races. HLA-A*03, Cw*05, DRB1*01, DQB1*03 and DQB1*05 are associated with viral clearance while HLA-DRB1*07 and DQB1*02 are risk markers for viral persistence of HCV infection in Midwestern Americans. These results reveal ethnically and geographically different distribution of HLA-genes which are associated with the outcome of HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 30 publications
(46 reference statements)
4
41
1
Order By: Relevance
“…Other studies have also identified HLA-A*03 as a critical determinant of outcome in HCV and hepatitis B virus (HBV). Wang et al describe an association between viral clearance and HLA-A*03; however, this association was only identified in the non-Caucasian subgroup of the cohort 34. In a Korean study, HLA-A*03 was found significantly more frequently in chronic HCV carriers compared with healthy controls 35.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have also identified HLA-A*03 as a critical determinant of outcome in HCV and hepatitis B virus (HBV). Wang et al describe an association between viral clearance and HLA-A*03; however, this association was only identified in the non-Caucasian subgroup of the cohort 34. In a Korean study, HLA-A*03 was found significantly more frequently in chronic HCV carriers compared with healthy controls 35.…”
Section: Discussionmentioning
confidence: 96%
“…Studies also showed the importance of HLA molecules to the natural outcomes of HCV infection. Although it has been reported in a few sufficiently sampled and well-designed studies that some alleles have strong associations with HCV infection [10,1618], many other studies were limited either due to a small study population, or an inappropriate population stratification, or the lack of correction for multiple comparisons, or a low resolution typing technique [5,19]. Moreover, racial differences in the studies of association between the HLA patterns and the outcomes of HCV infection were also identified [1821].…”
Section: Introductionmentioning
confidence: 99%
“…For analysis, liver fibrosis was also classified either being mild (0-2), moderate (3)(4) or severe (5-6). Activity was graded into minimal (0-4), mild (5-8), moderate (8)(9)(10)(11)(12) and severe (13)(14)(15)(16)(17)(18)). All patients were tested negative for both hepatitis B surface antigen (HBs antigen) and anti-HIV antibody.…”
Section: Methodsmentioning
confidence: 99%
“…on the associations between HLA Class II alleles and HCV infection [12]. In addition, the reported associations showed ethnic and geographical differences [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%